Managing Life‐Threatening Tracheal Malignancy and Lung Metastases in a Young Woman: A Case of Aggressive Airway Intervention - Rahul Kumar Chaudhary; Anuja Pokharel; Sangeeta Subba; Kumud Pyakurel; Rojina Sedhai; Lalit Kumar Rajbanshi; Sajjad Ahmed Khan (Clinical Case Reports)
ABSTRACT Infiltrative tracheal malignancies are exceptionally rare among younger individuals, but when they do occur, they present a significant and immediate risk due to severe airway compromise. Managing the airway in such cases is extremely challenging in low‐resource settings and requires a highly skilled team of anesthesiologists utilizing advanced techniques. This case report outlines the airway management of a patient with an infiltrative tracheal malignancy who experienced severe airway obstruction. In such situations, definitive airway control often necessitates an emergency tracheostomy. One effective approach includes performing emergency intubation with a small cuffed endotracheal tube, followed by a low tracheostomy, with the assistance of fiberoptic bronchoscopy to ensure safe airway management.